Study on Sheep Animal Welfare in Traditional Farmer, Located in Agro Edutourism Mulyaharja Bogor Regency - Astini, Wining; Endah Anggraeni, Henny; Barunawati Siagian, Tetty; Sulistiawati, Erni; Vibowo, Heryudianto; Wijaya Kusuma, Surya; Budiono, Dwi; Fardesiana Putri, Miranti; Zahidah, Siti; Haikal, Muhammad; Faisal, Agus (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2025)
Indonesian farmers do not understand about the meaning of animal welfare. It makes to be difficult to implement the animal welfare. It also impacts to the production and reproduction of the animal. On the other side, the sheep livestock in Mulyaharja are maintained traditionally. This study aims to evaluate the implementation of animal welfare principle in traditional sheep farming in Mulyaharja subdistrict. This study used purposively sampling. The data analysis method is descriptive by processing data from interviews. The Animal Needs Index were used in this study. This study highlights significant shortcomings in sheep welfare under traditional farming practices in Mulyaharja Subdistrict with average ANI index 16.49. Targeted interventions in comfort of the lie down, number days of outside/year, pasture months/year, comfort of flooring, cleanliness sheep and pen, slipperiness, ease of passage, quality of light, quality of air and air flow, ind exposure in the lying area, condition of integument and animal health.